Features of formation and implementation of strategic priorities for security and development of Ukraine and the Republic of Poland - Novikova, Olga; Pankova, Oksana (Contemporary trends in business security: Problems and challenges of eastern economies, 2022)
Specific features of shaping and modification of national security models of Ukraine and the Republic of Poland are determined, the content of the legal framework that defines the security and development strategies of these countries is revealed. The expediency of developing a new essence and structure of strategic documents that ensure social development and guarantees of security of man, society and state is substantiated. The aspiration and priority of the states' policy on their integration into the European Security Environment and NATO has been determined.